Rapid In vitro Root Induction in Transgenic - Rashid, Bushra; Husnain, Tayyab; Riazuddin, S. (Plant Tissue Culture and Biotechnology, 2010)
Key words: Gossypium hirsutum, Rooting, Transgenic cotton D.O.I. 10.3329/ptcb.v19i2.5442 <span style="font-size: 9pt; font-family: Palatino; mso-bidi-language: AR-SA; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-size: 12.0pt; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US;">Plant Tissue Cult. & Biotech. 19(2): 247-251, 2009 (December) <span style="font-size: 10pt; font-family: "Palatino Linotype"; mso-bidi-language: AR-SA; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US;">- Short communication